Keberhasilan Bayi Menemukan Puting Susu Ibu saat Inisiasi Menyusu Dini - I Dewa Ayu Ketut Surinati; Sur Suratiah (Jurnal Gema Keperawatan, 2017)
The purpose of this research is to know Description Of Baby Success When Nipple Early Initiation Of Breastfeeding. The methode of this research was discriptif design. The samples were consisted of 56 respondents selected with Purposive samplingtechnique. The results of the study of 56 respondents found that most of the time the baby find the mother's nipple ≤1 hour, is 42 respondents ( 75 % ) or can be categorized either.